When the Frequencies of Sensitization and Elicitation of Allergic Reaction Do Not Correlate—The Case of Apple Gibberellin-Regulated Protein Tested in an Italian Population - Tuppo, Lisa; Alessandri, Claudia; Giangrieco, Ivana; Tamburrini, Maurizio; Arriaza, Ricardo Hernandez; Chruszcz, Maksymilian; Mari, Adriano; Ciardiello, Maria Antonietta (Frontiers in Allergy, 2021)
Background: The literature reports describing allergic symptoms against apples in the patients sensitized to the gibberellin-regulated proteins (GRPs) suggested the presence of an allergenic GRP in this fruit. Objective: This study aimed to assess the presence of a GRP protein in apples and investigate its allergenicity. Methods: The protein was isolated and identified by the classical biochemical methods. The bioinformatics tools were used for similar searches and molecular modeling. The immunological features were investigated using the multiplex FABER test. Clinical data were collected by the allergy specialists. Results: A GRP was detected in the apple peel and pulp and it was named applemaclein. This protein displays 94% of sequence identity with peamaclein, Pru p 7, representing the prototype of this allergen family. The applemaclein molecular model shows a very irregular surface with grooves/clefts that may potentially accommodate small molecular ligands. In a population of 4,721 patients in Italy, 187 (4.0%) were sensitized to any allergenic GPR. Of those, 115 (61.5%), 61 (32.6%), 30 (16.0%), and 99 (52.9%) had immunoglobulin E (IgE) to apple, peach, pomegranate, and cypress GRP, respectively. However, in a cohort of the patients in Italy, most individuals IgE positive to the apple GRP did not report allergic reactions against this fruit. Conclusion: Compared with the peach Pru p 7, applemaclein shows some different structural features and higher sensitization frequency, which is often not associated with allergic reactions against apple. Further studies are needed to understand a possible correlation between the applemaclein structural properties, the interaction with still unknown molecules, and immunological behavior.